Autosomal recessive postlingual hearing loss (DFNB8): compound heterozygosity for two novel TMPRSS3 mutations in German siblings. Issue 6 (5th June 2007) - Elbracht, Miriam; Senderek, Jan; Eggermann, Thomas; Thürmer, Christian; Park, Jonas; Westhofen, Martin; Zerres, Klaus
Abstract : Mutations in the transmembrane protease, serine 3 ( TMPRSS3 ) gene, encoding a transmembrane serine protease, cause autosomal recessive deafness childhood (DFNB8) or congenital onset (DFNB10). TMPRSS3 mutations have been mainly identified in patients from Asian and Mediterranean countries and seem to be a rare finding in the Northern European population so far. The identification of two novel pathogenic TMPRSS3 mutations (c.646C→T − R216C; c.916G→A − A306T) is described in four affected siblings of German origin with postlingual hearing loss, treated by bilateral cochlear implantation with good results. Although TMPRSS3 mutations are supposed to be a rare cause of autosomal recessive hearing loss, in families with postlingual disease onset TMPRSS3 is the most favourable candidate gene after exclusion of GJB2 mutations.